2007
DOI: 10.1007/s10494-007-9113-3
|View full text |Cite
|
Sign up to set email alerts
|

Mean Flow Structures Inside the Human Upper Airway

Abstract: The lattice Boltzmann method (LBM) was used to conduct a direct numerical simulation study of the airflow inside an idealised human upper airway. Results from both a modest resolution (18 million control volumes, 320 Gb data set) and an extreme resolution (148 million control volumes, 800 Gb data set) LBM simulation were compared to those from experimental results (Johnstone, A.: Hot wire measurements in an oropharyngeal pathway. M.Sc. Thesis, Queen's University, Kingston, ON, Canada, 2002; Johnstone et al., E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Other works, such as Jayaraju et al [6] and Ball et al [7], used the upper human airway with an idealized geometry and presented results concerning mean flow and flow structures. Contrary to Jayaraju et al…”
Section: Doorly Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Other works, such as Jayaraju et al [6] and Ball et al [7], used the upper human airway with an idealized geometry and presented results concerning mean flow and flow structures. Contrary to Jayaraju et al…”
Section: Doorly Et Almentioning
confidence: 99%
“…Many works have been performed with simplified models [11], idealized models [6,7], or using several realistic models [2,3], for example Choi et al [12] investigated the variabilities of intra-and inter-subject of airflow in the human lung.…”
Section: Doorly Et Almentioning
confidence: 99%
“…It has been used in simulating biomedical flows, such as flows in the respiratory system (Ball et al, 2008; Finck et al, 2007; Hörschler et al, 2010; Eitel et al, 2010; Lintermann et al, 2012) and cardiovascular system (Munn and Dupin, 2008; Boyd and Buick, 2008; Kim et al, 2010). The published LBM studies related to the UA are mostly concerned with the laminar flow in the nasal cavity (Finck et al, 2007; Eitel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated the capability of the LBM for predicting the complex flow in the UA. Recently, the DNS-LBM has been used to simulate the laminar-transitional-turbulent flows in an idealized laboratory model of the airway (Ball et al, 2008). The results of Ball et al showed that the DNS-LBM was superior to RANS as it reproduced the critical flow features observed in the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike former numerical and experimental investigations, in which a simplified geometry was used, the present method can be efficiently applied to variable, realistic airway geometries. For instance the flow field downstream of the laryngeal region has recently been investigated in [13] by an LBM. Since the numerical method is capable of reproducing small-scale features of lung flow, the results serve to fundamentally understand respiratory mechanisms.…”
Section: Introductionmentioning
confidence: 99%